2007
DOI: 10.1177/0898010107306199
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Theory for Nursing Education

Abstract: This article discusses how aspects of a holistic comfort theory were adapted to create a taxonomic structure to apply its concepts to a fast-track nursing education program. The principles of learner-centered education were combined with comfort theory to develop strategies that appear to have produced positive influences on the attributes and contexts of comfort within the learning community. With emphasis on balanced academic exposure to the art of comfort as well as the rigorous science of nursing, students… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 5 publications
0
8
0
1
Order By: Relevance
“…Although the analysis of the eigenvalues initially suggested 16 factors, the graphical results of the scree plot and Horn's Parallel Analysis were taken into consideration, indicating a construct of 4 to 5 factors. The explained variance analysis further indicated the predominance of factor 1 in relation to the others, leading to the test of the hypothesis of the construct's unidimensionality, which would go against it being understood as a multidimensional phenomenon, according to specialists on the issue 12 . Nevertheless, after this assumption was tested, the ECONF's unidimensionality was refuted; however, this may represent the relevance of the first factor for the explanation of the families' comfort.…”
Section: Discussionmentioning
confidence: 99%
“…Although the analysis of the eigenvalues initially suggested 16 factors, the graphical results of the scree plot and Horn's Parallel Analysis were taken into consideration, indicating a construct of 4 to 5 factors. The explained variance analysis further indicated the predominance of factor 1 in relation to the others, leading to the test of the hypothesis of the construct's unidimensionality, which would go against it being understood as a multidimensional phenomenon, according to specialists on the issue 12 . Nevertheless, after this assumption was tested, the ECONF's unidimensionality was refuted; however, this may represent the relevance of the first factor for the explanation of the families' comfort.…”
Section: Discussionmentioning
confidence: 99%
“…Glazer and Gyurak (2008) examined sources of occupational stress, and identified three areas that need to be satisfied to reduce nurses' anxieties, appreciation of the task to be performed, the type of patient who is going to perform the task, and the skill set of the staff involved. Similarly, Goodwin et al (2007) identified the need for nurses to be 'prepared', and to 'know that their patients would be safe' to reduce their anxieties. The participants in this study expressed anxieties related to all these areas.…”
Section: Discussionmentioning
confidence: 99%
“…The comfort theory explains comfort in 3 different forms, namely freedom, peace and conditions which are above optimal [11]. This comfort dimension is defined by Kolcaba holistically as an experience that immediately gives rise to strength, with the achievement of the need to be free, peaceful and conditions above optimal in 4 contexts, namely physical, psychospiritual, sociocultural, and environment [5].…”
Section: Resultsmentioning
confidence: 99%